Eksistensi Alat Bukti Formal Dalam Perselisihan Hubungan Industrial - Hasan Al Munir; Asri Wijayanti (Faculty of Law, Universitas Wijayakusuma, 2020)
Abstract Formal evidence in industrial relations disputes is very important in fact the parties (workers) are unable to provide sufficient formal evidence during the process of resolving industrial relations. The purpose of this research found out the substance of legal subjects and legal objects of formal evidence in the process of resolving industrial relations disputes.Â This legal research was a normative juridical with a statute approach. The results showed the substance of formal evidence in industrial relations disputes, consisting of the substance of the legal subject and the legal object of the evidence. formal evidence in disputes over industrial relations was very important to achieve truth. The resulting recommendations were that special arrangements that needed to be made to require employers / laborers to provide evidence of industrial relations they carried out.Keywords: Evidence, Industrial Relations DisputesÂ AbstrakAlat bukti formal dalam perselisihan hubungan industrial sangat penting faktanya para pihak (pekerja) kurang dapat memberikan alat bukti formal yang cukup saat proses penyelesaian hubungan industrial. Tujuan penelitian ini adalah untuk mengetahui substansi subyek hukum dan obyek hukum dari alat bukti formal dalam proses penyelesaian perselisihan hubungan industrial. Penelitian hukum ini adalah yuridis normatif dengan pendekatan statute approach.Hasil penelitian adalah subtansi alat bukti formal dalam perselisihan hubungan indusrtial,terdiri atas substansi subyek hukum dan obyek hukum dari alat bukti.alat bukti formal dalam perselisihan hubungan idustrial sangat penting untuk mencapai kebenaran. Rekomendasi yang dihasilkan adalah perlu pengaturan khusus untuk mewajib kanpengusaha/pemberi kerja dalam memberikan alat bukti formal atas hubungan industrial yang dilaksanakannya.Kata Kunci : Alat Bukti, Perselisihan Hubungan IndustrialÂ